2017
DOI: 10.1016/j.jss.2017.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ischemic muscle in patients with peripheral artery disease using X-ray spectroscopy

Abstract: Background Peripheral artery disease (PAD) is a vascular disease caused by atherosclerosis resulting in decreased blood flow to the lower extremities. The ankle brachial index (ABI) is a standard PAD diagnostic test, but only identifies reduced blood flow based on blood pressure differences. The early signs of PAD manifest themselves not only clinically, but also at an elemental and biochemical level. However, the biochemical and elemental alterations to PAD muscle are not well understood. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Copper deficiency causes muscle weakness and anaemia. Zinc, as an antioxidant that affects the development and regeneration of muscle tissue, also stabilises the protein structures from which fibres are made [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper deficiency causes muscle weakness and anaemia. Zinc, as an antioxidant that affects the development and regeneration of muscle tissue, also stabilises the protein structures from which fibres are made [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Copper deficiency causes muscle weakness and anaemia. Zinc, as an antioxidant that affects the development and regeneration of muscle tissue, also stabilises the protein structures from which fibres are made [9][10][11][12][13][14]. In order to find out which elements have the greatest influence on differentiation, a multivariate discriminate analysis (MDA) was performed for the analysed fibres.…”
Section: Resultsmentioning
confidence: 99%
“…Other non-invasive imaging modalities have characterised PAOD lesions, e.g., Becker et al used xray spectroscopy to compare fundamental changes in intracellular elemental compositions between control, claudicants, and critical limb ischaemia muscle tissue. 30 The study showed that intracellular magnesium and calcium were lower in PAOD compared with control myofibres, whereas sulphur was higher. A combination of microCT with evaluation of the muscles of the ischaemic leg could lead to greater accuracy and better understanding of PAOD.…”
Section: Microct a Step Closer To Histological Characterisation And To Clinical Applicationsmentioning
confidence: 90%
“…However, it is important to report that these techniques allow researchers to simultaneously detect magnesium and other trace elements in several tissues. Clinical application of analytical scanning electron microscopy (ASEM) using computerized elemental x-ray analysis on sublingual epithelial cells was used for the simultaneous detection of magnesium and potassium in diabetes patients treated with magnesium supplementation [ 287 ]; energy dispersive x-ray spectroscopy coupled to scanning electron microscopy enables researchers to quantify differences in elemental composition in muscle biopsies of patients with peripheral artery disease (PAD), finding significative difference particularly in calcium, magnesium, and sulfur content, while C, O, K, and Na do not change within the different samples [ 288 ].…”
Section: Methods To Evaluate Magnesium Statusmentioning
confidence: 99%